A comprehensive study on the fruit quality of a late-ripening mutant variety of plum - Huifen Zhang; Ying Du; Yinyin Meng; Xiaofu Tang; Jie Niu; Hongxia Wang; Yihua Ren; Penghan Yi; Xian Luo; Qunxian Deng (Food Chemistry: Molecular Sciences)
The fruit ripening period is an important factor affecting fruit quality and commercial value.To investigate why WSQCL ripens about 15 days later than QCL and why WSQCL has a more astringent flavor. This study analyzed the dynamics of fruit development and quality of three plum varieties, including “Late-maturing Qiangcuili” (WSQCL), ‘Qiangcuili’ (QCL), and ‘Cuihongli’ (CHL), to explore the differences in plums quality formation and the ripening period between the late-maturing variant WSQCL and its parental cultivars. The results indicated that the order of the fruit growth rate was QCL > WSQCL > CHL. During fruit development of the three plum varieties, the changes in soluble sugar (SS), titratable acid (TA), starch, chlorophyll, carotenoids, and phenolic contents were consistent, while the accumulation of total phenols, SS, and TA differed significantly between WSQCL and QCL. WSQCL had higher expression of genes related to phenolic compound synthesis than QCL, and phenolic compound synthesis was closely associated with the expression of PAL3, 4CL, HCT1, and CHS. Principal component analysis revealed differences between WSQCL and the other two varieties during the middle and late stages of fruit development. This study provides a reference for quality formation and development of the potential value of WSQCL.